Effectiveness of sequential viscosupplementation in temporomandibular joint internal derangements and symptomatology : a case series - Fonseca, Roberta Maria Drumond Furtado Bossi (2018)
Viscosupplementation is a minimally invasive technique that replaces synovial fluid by intra-articular injection of hyaluronic acid (HA). Although effective in some joints, there is not conclusive evidence regarding temporomandibular disorders. +is case series described the efficacy of a viscosupplementation protocol in intra-articular temporomandibular disorders. Ten patients with a diagnosis of disc displacement and/or osteoarthritis by Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) were submitted to four monthly injections of low or medium molecular weight HA. Pain, mandibular function, image analysis by tomography and magnetic resonance, and quality of life were assessed at baseline and follow-ups (1 and 6 months). Pain, jaw range-of-motion, mandibular function, and quality of life improved at follow-up evaluations. Osteoarthritis changes decreased, and 20% of patients improved mandibular head excursion after treatment. Resolution of effusion and improvement in disc morphology were observed for most patients. +is viscosupplementation protocol reduced pain and symptoms associated with internal derangement of temporomandibular joint, improved quality of life, and showed benefits from both low and medium molecular weight HA in alternate cycles.